DUALISME HUKUM PERKAWINAN DAMPAKNYA TERHADAP PEREMPUAN - Faridy Faridy; Idrus Ali; Wahyu Wulan Suci (JURNAL HAKAM, 2022)
A sirri marriage is one in which the woman's guardian marries a man in front of two witnesses, but the marriage is not reported or registered with the Office of Religious Affairs (KUA). Marriage registration, in this situation, is covered by the law that governs the duty to register with the Marriage Registrar, which can be found in either the Marriage Law or the KHI (Islamic Law Compilation). Thus, if a marriage satisfies the elements of religious procedures and marriage registration procedures based on the norms established by the legislation, it can be considered legal activity. Sirri's marriage is invalid from a legal standpoint because there is no guarantee that it will benefit the establishment of the household without marriage registration and verification with a marriage certificate. Furthermore, on a religious level, it adheres to the Islamic law principles/rules that denying injury takes precedence over getting advantage.